A highly integrated dual-band triple-mode transmit IC for cellular CDMA2000 applications. - Aggarwal, S. (IEEE Journal of solid state circuits)
A highly integrated transmit integrated circuit intended for dual-band (CELL/PCS) and triple-mode (CDMA/TDMA/AMPS) cellular mobile stations is presented. It features a linear-in-dB gain-control range of 90 dB and provides a high output power of 9 dBm (PCS band) while meeting linearity requirements (-53-dBc ACPR) and achieving the receive-band noise floor of -133 dBm/Hz. It consumes only 130-mA current (3-V supply) in the PCS band. A dynamic-biasing feature results in additional power savings at lower signal levels. The circuit is fabricated in a 30-GHz fT BiCMOS technology.